Selective laser melting of weak-textured commercially pure titanium with high strength and ductility: A study from laser power perspective. (15th February 2017) - Li, X.P.; Van Humbeeck, J.; Kruth, J.P.
Abstract: In this study, fully dense commercially pure titanium (CP Ti) parts were successfully fabricated by selective laser melting (SLM) using the same optimal laser energy density E p ¯ but with two different laser powers: high laser power E H 250 W and low laser power E L 50 W. It was found that at the same E p ¯ different laser powers led to different phase formation, microstructure, texture and mechanical properties of the selective laser melting fabricated (SLMed) CP Ti. A weak-textured CP Ti with isotropic mechanical properties was achieved using E H while a strong-textured CP Ti with anisotropic mechanical properties was obtained using E L . The underlying mechanism was attributed to the formation of α' phase in the CP Ti as a result of the higher cooling rates at E H . The formation of α' phase also contributed to the observed high ultimate compressive strength 1.1 GPa and high compressive strain ≥ 50% in the SLMed weak-textured CP Ti at E H . This study provides important insights into the role of laser energy in the SLM fabrication of CP Ti with tailorable crystallographic texture and thus mechanical properties. Graphical abstract: Highlights: Different laser powers led to different phase formation, microstructure, texture and mechanical properties of SLMed CP Ti. A weak-textured CP Ti with isotropic mechanical properties was achieved using high laser power A strong-textured CP Ti with anisotropic mechanical properties was obtained using low laser power The mechanism was attributed to the formation of α′ phase as a result of the higher cooling rates at high laser power. The weak-texture CP Ti showed high ultimate compressive strength 1.1 GPa with a compressive strain ≥ 50%